Case Study: Audit Building of Person with Disable (PWDS) on Selected Klinik Kesihatan in Negeri Johor - Abu Hassan, Nur Farah Shuhada; Musa, Ir. Ts. Dr. Mohd Kamaruzaman (Progress in Engineering Application and Technology, 2022)
In Malaysia, the disabled (PWDs) are continuing to increase from 2018 to 2021 and this community is a group of the worldwide people who should be given an opportunity to enjoy the same life as the normal group on the basis of full equality. People with disabilities do not even have equality in the facilities offered in a place, particularly in public spaces; some places consider these facilities to be unimportant, although this is incorporated in the Malaysian Standard. This problem develops when most people with disabilities facilities are not equipped to meet the needs of the disabled and the universal design is not properly adapted. As a result of the lack of amenities for this group, it has inhibited the desire of individuals with disabilities to continue to use public facilities or be in public locations. The purpose of this research is to learn about the facilities available in Klinik Kesihatan for people with impairments. Second, the study’s goal was to identify the people with disabilities facilities that were supplied in compliance with the rules that had been created for Klinik Kesihatan and, finally, to review the sorts of disabled facilities that were available in Johor Klinik Kesihatan. This study used the primary and secondary methods, with assessments performed at a Klinik Kesihatan using a checklist based on the Malaysian Standard Set. The findings indicate that facility design is not user-friendly and is merely in accordance with the criteria of the Uniform Building By-Laws (UBBL).